SOME BACTERIAL CHANGES OF LOCAL AND IMPORTED FROZEN CHICKEN MEAT - F. Tamerkhan (Mesopotamia Journal of Agriculture)
This study was carried out in order to evaluate bacterial content at each thorax and thigh pieces for kinds of domestic and imported ( Turkish & Brazilian) chicken meat which stored at -18C and -22C for 150 days , this changes including bacterial total count , coliform, psychrophylic, protolytic and lipolytic bacteria were conducted each 30 days . Results showed significant differences (P<0.05) in the properties of all kinds of chickens between thorax and thigh pieces at both temperatures (-18C and-22C) also there was significant decrease in bacterial content with increasing the freezing periods for all kinds of chickens and the bacterial count of the frozen samples stored at –22C less than that at -18C while the interaction effects of all the studied factors on bacterial content found to be significant.